A produção de gêneros escritos no exame de proficiência de língua portuguesa para estrangeiros - Lúcia Péret Dell´Isola , Regina (Revista Vozes dos Vales: Publicações Acadêmicas, 2025)
The official examination of proficiency in Brazilian Portuguese for foreigners (CELPE-Bras) is guided in activities socio interactionists evaluated through communicative tasks. Examinees are submitted for execution of tasks by means of which must prove their proficiency in Brazilian variant of Portuguese. In this article, based on the theory of Swales (1994, 1998) and the concept of gender as social action, as proposed Bazerman (1994, 2005), we analyzed 35 letters to the editor produced by the examinees Celpe-Bras, in performing the task IV the second application of the test in 2008. This task was to read a report in the magazine "IstoÉ" and write text to be published in the letters section of the reader of the same magazine.